2018
DOI: 10.1111/bju.14202
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low‐intensity extracorporeal shockwave therapy in an obesity‐associated erectile dysfunction rat model

Abstract: ZF rats can serve as an animal model in which to study OAED. This study reveals that obesity impairs erectile function by causing smooth muscle atrophy, endothelial dysfunction, and lipid accumulation in the corpus cavernosum. Li-ESWT restored penile haemodynamic parameters in the ZF rats by restoring smooth muscle and endothelium content and reducing lipid accumulation. The underlying mechanism of Li-ESWT appears to be activation of stem/progenitor cells, which prompts cellular proliferation and accelerates p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Evident demonstrated that mechanical forces direct tissue development, morphogenesis, and regeneration, 33 while low-intensity extracorporeal shock wave therapy (Li-ESWT), as a mechanical force, activated penile stem cells, 20 and increased phosphorylated histone 3 (H3P) level. 21 Very recently, we reported that MAP effectively improved vaginal distension induced SUI. 22 We also successfully applied MAP to an OA-SUI rat model and improved the stress incontinence (In manuscript Part I).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Evident demonstrated that mechanical forces direct tissue development, morphogenesis, and regeneration, 33 while low-intensity extracorporeal shock wave therapy (Li-ESWT), as a mechanical force, activated penile stem cells, 20 and increased phosphorylated histone 3 (H3P) level. 21 Very recently, we reported that MAP effectively improved vaginal distension induced SUI. 22 We also successfully applied MAP to an OA-SUI rat model and improved the stress incontinence (In manuscript Part I).…”
Section: Discussionmentioning
confidence: 96%
“…In situ activation of tissue resident satellite cells within the urethral and pelvic floor muscle is an exciting potential therapy for OA‐SUI that avoids these potentially significant negative consequences of exogenous stem cell therapy. Evident demonstrated that mechanical forces direct tissue development, morphogenesis, and regeneration, while low‐intensity extracorporeal shock wave therapy (Li‐ESWT), as a mechanical force, activated penile stem cells, and increased phosphorylated histone 3 (H3P) level . Very recently, we reported that MAP effectively improved vaginal distension induced SUI .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an animal model of severe injury to cavernous and pudendal nerves and internal pudendal arteries, LI-ESWT improved intracavernous pressure by enhancing angiogenesis, tissue restoration, and nerve regeneration with activation of Schwann cells and endothelial cells [2]. In an animal model of obesity-associated ED with smooth muscle atrophy, endothelial dysfunction, and lipid accumulation within the corpus cavernosum, LI-ESWT restored penile hemodynamic parameters in obese rats by restoring smooth muscle and endothelium content and reducing lipid accumulation [3]. The mechanism underlying the effect of LI-ESWT appears to be activation of resident stem/progenitor cells, which prompts cellular proliferation and accelerates penile tissue regeneration [4].…”
mentioning
confidence: 99%